IMPLEMENTASI PROGRAM PELAJAR TANGERANG MENGAJI (PTM) DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK DI SEKOLAH DASAR - Fatmala, Nabila; M. Taufik; Ngulwiyah, Istinganatul (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Religious character is essential in shaping students’ personalities through values such as obedience in worship, honesty, discipline, and mutual respect. This study aims to examine the planning, implementation, and impact of the Pelajar Tangerang Mengaji (PTM) program in fostering students’ religious character at SDN Cibodas 8 Kota Tangerang. The problem underlying this research is that some students still show a lack of discipline, have not been consistent in applying religious values outside PTM activities, and show limited respect for peers during Qur’an recitation and dhuha prayer. PTM is a daily routine before lessons begin, consisting of Qur’an recitation and congregational dhuha prayer. This study employed a descriptive qualitative approach using observation, interviews, and documentation. The findings indicate that PTM was designed through collaboration between the principal, islamic education teachers, and other school staff. Its implementation ran orderly and received positive responses from students. The program had a positive impact on increasing students’ obedience to worship, sincerity, self-confidence, creativity, responsibility, honesty, and discipline, although respect for others still requires further development. Overall, PTM serves as an effective means to instill religious values and shape students’ character from an early age.